Whole Body Mechanical Vibrations of Passengers Travelling in Busses in Sri Lanka - Wijesiriwardana, R.; Vignarajah, M.; Kathirgamanathan, P.; Gnanasena, T.U.; Dissanayake, D.M.P.C. (Institute of Research Engineers and Doctors, 2018)
Abstract— One of the main passenger transportations in Sri Lanka is the bus. Most of these busses used for the passenger transportation do not have proper vibration dampers and passengers who travel in them are subjected to severe vibration levels as most of the time they are travelling standing up rather than sitting down on comfortable seats. Sever vibration levels produced by the engines of the busses and the poor road conditions in Sri Lanka are directly transfer to the passengers due to poor vibration damping of the busses. This paper discusses the vibration levels that the passengers travelling in Sri Lankan busses encounter by using accelerometers and the mechanical modelling of the passenger whole body vibrations. A new model is put forward to account for the nonlinear effects. Also the paper compares the passenger vibration levels with the international standards for safer passenger vibration levels (ISO2631). First part of the paper discusses the power spectral densities of the vibrations generated in the busses and also transferring from the road on to different locations of the busses where the passengers are normally travelling. Also the paper further discusses improved lumped parameter based mechanical dynamics model for standing up travelers subjected these vibrations, catering for the nonlinear effects by using additional viscous springs and dampers. Final part of the paper discusses the effectiveness of the use of commonly available elastic soles, elastic insert pads or elastic slippers foot ware to reduce the harmful vibrational effects of frequent travelers.
Keywords: Whole body vibration; Passenger bus; ISO2631